2019
DOI: 10.2147/ott.s222702
|View full text |Cite
|
Sign up to set email alerts
|

<p>High-dose vitamin C suppresses the invasion and metastasis of breast cancer cells via inhibiting epithelial-mesenchymal transition</p>

Abstract: PurposeVitamin C (VC) is a kind of essential nutrient in the body regarded as a canonical antioxidant during the past hundred years. However, the anti-cancer effect of VC is controversial. Our study is trying to clarify the relationship between VC dosage and breast cancer metastasis.MethodsHuman breast cancer cell lines Bcap37 and MDA-MB-453 were treated with VC at three different concentrations (low-dose, 0.01 mM; medium-dose, 0.1 mM; high-dose, 2 mM). Wound healing assays were conducted for migration assay; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 39 publications
1
41
0
2
Order By: Relevance
“…Loss of extracellular matrix adhesion in primary cancer cells leads to intravasation, releasing CTCs. Studies suggested potential roles of vitamin C in preventing breast cancer metastasis via the regulation of the extracellular matrix [ 151 , 152 ]. An electron from vitamin C can be used to reduce ferric iron to ferrous iron, and this supports the action of lysyl hydroxylase and prolyl hydroxylase, iron binding enzymes required during collagen synthesis.…”
Section: Antioxidant and Breast Cancer Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of extracellular matrix adhesion in primary cancer cells leads to intravasation, releasing CTCs. Studies suggested potential roles of vitamin C in preventing breast cancer metastasis via the regulation of the extracellular matrix [ 151 , 152 ]. An electron from vitamin C can be used to reduce ferric iron to ferrous iron, and this supports the action of lysyl hydroxylase and prolyl hydroxylase, iron binding enzymes required during collagen synthesis.…”
Section: Antioxidant and Breast Cancer Metastasismentioning
confidence: 99%
“…Transgenic mice lacking gulonolactone oxidase, a key enzyme for vitamin C synthesis, showed a poorly defined collagenous barrier, whereas vitamin C supplemented mice showed optimal extracellular matrix formation [ 151 , 153 ]. Treatment with a high (millimolar) concentration of vitamin C increased protein levels of E-cadherin, a key protein for cell-extracellular matrix adhesion in the BCap-37 human breast cancer cell [ 152 ]. Micromolar levels of vitamin C impaired the assembly of the actin filament via downregulation of YAP1, and this decreased motility of MDA-MB-231 cells [ 154 ].…”
Section: Antioxidant and Breast Cancer Metastasismentioning
confidence: 99%
“…Several previous studies have reported that administration of a daily dose of 10 g L-AA has a beneficial effect in patients with cancer [28][29][30][31], while some have reported no overall relationship with L-AA intake [32][33][34]. Regarding this controversy, several reports have noted that the administration route of high-dose of L-AA (oral or intravenous injection) is crucial [35]. Intravenous injections of L-AA are maintained at high level in the blood [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…For example, oral vitamin C supplementation blocks murine breast cancer metastasis in Gulo knockout mice, which like humans, cannot synthesize vitamin C [6]. High doses of vitamin C via intraperitoneal injection inhibit metastasis of human breast cancer xenografts in nude mice [7], which, like the Gulo wild-type mice, maintain endogenous vitamin C at~50 µM in the plasma [8]. Our earlier work also showed that oral vitamin C supplementation blocks human triple-negative breast cancer (TNBC) xenograft metastasis in mice [9].…”
Section: Introductionmentioning
confidence: 99%